Perawatan dan Perbaikan Sistem Kopling Manual Beberapa Jenis Mobil Operasional PT. Delta Sarana Sentosa - Qirul Nur Arianto; Iyan; La Ode Muhamad Dirman; Ferdin; Aminur (Piston: Jurnal Teknologi, 2023)
The manufacture of clutch components from the factory has an estimate or limit of the use of clutch components that must be replaced if any damage occurs. The purpose of this observation is to find out how to maintain and repair the manual clutch system, and find out the problems that often occur when the manual clutch system is operated. To identify or find out the damage to the components of the manual clutch system, the type of qualitative data is used, namely data that is explanations and descriptions that are described. This type of Quantitative data is data that is a number obtained from informants such as age and date of birth. The results of observations show that the components that often experience damage to the manual clutch system on Hino FM 260 FM cars, Isuzu NKR 71 HD cars, and Hino Dutro 130 HD cars are upper clutch master rubber, booster rubber (wind clutch), lower clutch master rubber and clutch lining. What makes the clutch slip is the worn-out clutch lining and the high clutch pedal. The causes of clutch lining wear out quickly are excessive clutch use, transporting loads that exceed capacity and uneven or difficult road terrain. The observation report contributes advice to users of PT DSS operational vehicles in maintaining and repairing their vehicle units.